2002
DOI: 10.1029/2001jd001403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an organic coating on marine aerosol particles by TOF‐SIMS

Abstract: [1] Marine aerosol particles play an important role in atmospheric processes. It has been suggested that as marine aerosol particles form, they acquire a coating of organic surfactants. This theory has been supported only by indirect evidence. Recently, we gave new morphological indication of such organic coating without however providing molecular speciation. Here we have studied the surface of marine aerosol particles by time-of-flight secondary ion mass spectrometry (TOF-SIMS), which is very suitable for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
179
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(185 citation statements)
references
References 41 publications
5
179
0
1
Order By: Relevance
“…Furthermore, there were peaks with large mass to charge ratios in the spectra, which indicate that some organic macromolecules or ion groups were created. During static TOF-SIMS, some molecular ions or ion groups might be induced from characteristic compounds on the surfaces of the samples, such as H 2 SO 4 , NH 4 HSO 4 , (NH 4 ) 2 SO 4 , NH 4 NO 3 , NH 4 Cl, NaNO 3 , and (NH 4 ) 2 SO 4 ·MSO 4 (M represents a metallic element) as well as short-or middle-chain organic alkyl compounds (like short-or middle-chain fatty acid compounds) (Tervahattu et al, 2002). Others are secondary compounds formed in the atmosphere, i.e., products of gases transforming to low volatile compounds (Harrison and Grieken, 1998;Peterson and Tyler, 2002).…”
Section: Classification Of Static Tof-sims Peaksmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there were peaks with large mass to charge ratios in the spectra, which indicate that some organic macromolecules or ion groups were created. During static TOF-SIMS, some molecular ions or ion groups might be induced from characteristic compounds on the surfaces of the samples, such as H 2 SO 4 , NH 4 HSO 4 , (NH 4 ) 2 SO 4 , NH 4 NO 3 , NH 4 Cl, NaNO 3 , and (NH 4 ) 2 SO 4 ·MSO 4 (M represents a metallic element) as well as short-or middle-chain organic alkyl compounds (like short-or middle-chain fatty acid compounds) (Tervahattu et al, 2002). Others are secondary compounds formed in the atmosphere, i.e., products of gases transforming to low volatile compounds (Harrison and Grieken, 1998;Peterson and Tyler, 2002).…”
Section: Classification Of Static Tof-sims Peaksmentioning
confidence: 99%
“…Therefore, the peaks of secondary ions demonstrate that there are compounds with these constituent ions on the surfaces of the samples, comprising secondary compounds formed in the atmosphere and organic compounds with alkyl groups. Both compound types influence the hydrophobic and hydrophilic surface characteristics of aerosol particles (Tervahattu et al, 2002;Richard and Bonnie, 2002), affecting the chemical behavior of these aerosol particles. Given the functional limitations of the instrument used in this study, not all of the secondary ions on the surface of aerosol particles were identified.…”
Section: Classification Of Static Tof-sims Peaksmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The organics include many different types of compounds, including phospholipids. [8][9][10][11][12][13][14][15][16] Some of the SSA particles redeposit into the ocean, while others are entrained upwards and can remain in the atmosphere up to several days. 5 During this time, SSA particles are exposed to atmospheric oxidants, such as the hydroxyl radical (OH), ozone, chlorine atoms and the nitrate radical (NO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The air-water interface (atmospheric aerosols in particular) has previously been proposed to be important in prebiotic chemistry (11)(12)(13)(14) because it provides a unique environment for chemistry through its ability to concentrate and align biochemical precursors and to alter the state of ionization of surface species (15)(16)(17)(18)(19). Contemporary marine aerosols have been found to contain the amino acid precursors necessary for peptide bond chemistry (20), enabling the possibility for their use in such reactions.…”
mentioning
confidence: 99%